Pengaruh Relationship Manager, Holistik, Internal Marketing terhadap Loyalitas Konsumen pada Toko Retail Bandar Lampung - Riki Wahyu Ramadhan; Lestari Wuryanti; Ayu Nursari (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the effect of Relationship Manager, holistic marketing, and Internal Marketing on customer loyalty in retail stores in Bandar Lampung. The increasingly competitive retail industry requires companies not only to focus on sales but also on managing sustainable customer relationships. An integrated marketing approach through the role of Relationship Managers, the implementation of holistic marketing, and Internal Marketing strategies is believed to enhance customer satisfaction and loyalty. This research employs a quantitative approach using a survey method by distributing questionnaires to 142 respondents who are retail store customers in Bandar Lampung. The sampling technique used was purposive sampling. Data analysis was conducted through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS software. The results indicate that partially, Relationship Manager, holistic marketing, and Internal Marketing have a positive and significant effect on customer loyalty. Simultaneously, these three variables also have a positive and significant impact on customer loyalty. Internal Marketing is found to be the most dominant variable influencing customer loyalty. This study provides theoretical contributions to the development of integrative marketing concepts and practical contributions for retail management in formulating effective strategies to enhance customer loyalty amid increasing business competition.